Орален мукозитис - компликација на високодозна хемотерапија и трансплантација на матични клетки - Стојаноски, Злате; Георгиевски, Борче; Генадиева-Ставриќ, Соња; Пивкова, Александра; Чадиевски, Лазар (SHMSHM / AAMD, 2011)
Oral mucosistis is one of the most frequent complications in early post-transplant period after high-dose chemotherapy and stem cell transplantation. As result of toxic demage oral and gastrointestinal mucosal barier due to high dose chemotherapy, transplanted patients are at high risk of infective complications, sepsis, high-mortality and prolonged hospitalisation. Aim of study: to evaluate frequency of oral mucositis in our group of patients treated with higu dose hemotherapy and stem cells transplantation at University clinic of hematology, medical faculty Skopje, R.Macedonia. Material and method: during a 10 years period (from September 2000 to September 2010 we have performed 200 stem cell transplntations in patients with different hematological malignancies. Male 112 Female 88 Mediane age 34 years. (from 9-63 years). Distribution according to diagnosis AML 62%, ALL 8%, MM 10%, HD 8%, NHL 8%, other 2%. High-dose chemotherapy was used according to underlying disease. Median number of infused CD34 + cells= 3,42 x 10/6/ Kg bw. Engraftment was established on day +12. Standard prophylactic strategies in our center is to prepare oral solution consisted: hexaetidin, nystatin, lidocain and NHCO3. Results: oral mucositis is present in 50% of the patients. According to WHO scale system: 10pts gr.4, 15 pts gr.3, 30pts gr.2, 45 patients gr 1. oral mucositis. Conclusions: the frequency of mucositis in our center is sligtly lower than results from literature. This is probably due to oral solution prepared in our center. Application of New drug palifermin will further decreased the incidence of oral mucositis, incidence of infective complications and mortality in this group of patients.
Oral mucositis- complications of high-dose chemotherapy in stem cell transplantation
Keywords: stem cell transplantation; oral mucositis